Diagnostic performance of cheeks appearance in sleep apnea. Issue 4 (4th July 2018) - Prikladnicki, Aline; Martinez, Denis; Brunetto, Melissa Giacomelli; Fiori, Cintia Zappe; Lenz, Maria do Carmo Sfreddo; Gomes, Erissandra
Abstract: Objective: Obstructive sleep apnea (OSA) is a common, potentially life-threatening, but underdiagnosed condition. The study aimed to test the role of facial myofunctional alterations in OSA screening. Method: Sixty-one individuals with sleep complaints were evaluated by the Orofacial Myofunctional Evaluation with Scores (OMES) protocol before undergoing polysomnography. The performance of each of the protocol scores in OSA screening was tested. Results: The nonparametric correlation of the apnea-hypopnea index (AHI) was significant for 18 of the 41 variables of the OMES protocol. Cheeks appearance had the best performance, increasing five times the odds for AHI ≥ 15. Its sensitivity was 66%; specificity, 72%; the area under the ROC curve, 0.69; positive and negative likelihood ratios, respectively, 2.38 and 0.47. Discussion: Cheeks appearance may be an instantly visible surrogate of tongue and pharyngeal fat deposition and of muscle function in OSA screening. Adding the item "cheeks appearance" to OSA screening tools and questionnaires may be useful for the identification of OSA risk.